Сomparison of biomechanical properties of non-absorbable and partially absorbable mesh implants used in surgery for urinary incontinence and genital prolapse: experimental study - D. D. Shkarupa; R. A. Shakhaliev; A. S. Shulgin; T. S. Filipenko; N. D. Kubin; I. A. Labetov; D. A. Suchkov (Вестник урологии, 2023)
Introduction. The amount of non-absorbable synthetic material used in the surgical treatment of pelvic organ prolapse and stress urinary incontinence has been shown to directly correlate with the risks of mesh-associated complications. Previously, we developed a partially absorbable implant. Currently, there are insufficient data on the use of partially absorbable implants in female pelvic floor reconstruction, which requires comparative biomechanical and pathomorphological studies.Objective. To compare the biomechanical properties of a new generation partially absorbable implants and nonabsorbable polypropylene mesh implants during animal model.Materials & methods. Thirty-nine rabbits weighing 3200 ± 250 g were randomised into three groups depending on the implanted endoprosthesis: group 1 (n = 15) — “Axilen” implant (polydioxanone 98%, polypropylene 2%), group 2 (n = 15) — “Axilen Rapid” implant (polyglycapron 98%, polypropylene 2%), group 3 (n = 9) — “Urosling 1” implant. After implantation, rabbits of all 3 groups were divided into 3 subgroups according to the withdrawal period from the experiment: 14 days, 60 days, and 180 days. The biomaterial obtained was subjected to two studies: evaluation of the macroscopic view of the explanted mesh endoprosthesis with the formed capsule and the surrounding tissues, study of the biomechanical properties of the formed connective tissue capsule with the implant.Results. According to macroscopic evaluation, there was a less significant tissue reaction to partially absorbed implants. A comparative analysis of biomechanical indices revealed no statistically significant difference in rupture elongation at all follow-up periods among the presented groups. Tensile strength, at 60 and 180 days, was not statistically different between the groups described. At 14 days, there was a statistically significant difference in tensile strength between groups 1 and 3 (p = 0.003).Conclusion. During biomechanical animal experiments, the connective tissue capsule formed on the partially absorbable implant was not inferior to the similar parameter of the non-absorbable sample in its tensile strength, which explains a great potential for the use of partially absorbable implants in reconstructive surgery of pelvic organ prolapse and stress urinary incontinence.